HIV Transmission Risk Behaviors Among People Living With HIV/AIDS. Issue 2 (March 2015) - Du, Ping; Crook, Tonya; Whitener, Cynthia; Albright, Patsi; Greenawalt, Daphne; Zurlo, John
<x xml:space="preserve">Abstract</x> Context: People living with human immunodeficiency virus (HIV)/AIDS (PLWHA) who continue high-risk behaviors may represent an important source for transmitting HIV infections. Objective: To identify factors associated with high-risk behaviors among PLWHA and to plan better HIV prevention intervention strategies in HIV care. Design: A cross-sectional survey to assess HIV transmission risk behaviors including sexual practices, disclosure of HIV infection status to sexual partner(s), and injection drug use. Setting: Five HIV outpatient clinics serving diverse PLWHA in south central Pennsylvania. Participants: A total of 519 HIV-infected patients. Main Outcome Measures: Two high-risk behaviors that may increase HIV transmission risk: (1) any unsafe sexual behavior and (2) nondisclosure of HIV infection status to sexual partner(s). An unsafe sexual behavior was defined as inconsistent condom use, sex under the influence of alcohol or drugs, or exchange of sex for money. A subgroup analysis was performed to examine factors related to unprotected anal intercourse among sexually active men who have sex with men. Results: About two-thirds of 519 HIV patients (65.7%) were sexually active, and nearly 50% of sexually active patients reported at least 1 unsafe sexual behavior. Nondisclosure of HIV infection status was reported by about 15% of the patients. Partners' characteristics including HIV infection status and the perceived partner behavior (ie, partner may have sex with other people) were significantly associated with unsafe sexual behaviors and with nondisclosure of HIV infection status. Non-Hispanic black males were more likely to withhold their HIV infection status from their sexual partner(s) (adjusted odds ratio = 4.51) than their white counterparts. In addition, the perceived partner sexual behavior was significantly related to unprotected anal intercourse among men who have sex with men (adjusted odds ratio = 2.00). Conclusions: High-risk sexual behaviors are commonly reported by PLWHA, and these behaviors may be influenced by their partners' characteristics. HIV prevention interventions and public health strategies need to be incorporated into HIV care.